Complex pricing and consumer-side transparency - Christian Fischer; Alexander Rasch (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We analyze a situation in which two horizontally differentiated firms compete in two-part tariffs (i.e., a linear and fixed price), and some consumers are not informed about the linear per-unit price. We show that there is a non-monotone relationship between the degree of consumer-side transparency and firm profits. Moreover, different from a situation without uninformed consumers, firms may make higher profits under two-part tariffs than under fixed fees only. There is also a non-monotone relationship between transparency and consumer surplus. Our model can explain why firms are against the abolishment of roaming fees and why the European Commission (EC) promotes it.
Keywords: D43; L13; L42; 330; fixed fee; linear price; roaming; transparency; two-part tariff